Worked to the Bone A Study of Gilded-Age Transatlantic Scientific Networks in Paleontology - Wendler, Philipp (Hamburg University Press, 2022)
In the American "Wild West" the nation's predominant paleontologists O. C. Marsh and E. D. Cope raced for the discovery of the most spectacular dinosaur fossils the world had ever seen. The "Bone Wars" not only unearthed triceratops, stegosaurus, and brontosaurus, they also made US paleontology world-famous. This book analyzes international scientific networks, carves out German influences on the evolution of US paleontology and higher education, and examines the link between the rise of US nationalism and science. So-far neglected by scholars, the perspectives of O. C. Marsh's German assistants take center stage.